Dracula - Stoker, Bram (Heinemann Publishers (Oxford) Ltd, 1992)
I looked up at the high castle walls. There were no lights in any of the windows. I heard the great wooden door being unlocked. It opened slowly. A very old man with white hair was standing there. Welcome to my home, he said. Enter Castle Dracula, Mr Harker. As I stepped inside, Count Dracula took hold of my arm. He was terribly strong and his hand was as cold as ice.
Keywords: Scary